2018
DOI: 10.1016/j.jgeb.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular studies on the effect of gamma radiation in fenugreek (Trigonella foenum-graecum L.) plants

Abstract: This experiment assessed the biochemical changes in fenugreek plants exposed to gamma radiation. Two pot experiments were carried out during two growing seasons of 2015 and 2016. Seeds were subjected to five doses of gamma irradiation (25, 50, 100, 200 and 400 Gy) and were immediately planted into soil pots in a greenhouse. The experimental analysis was performed in M1 and M2 generations. Significant differences between irradiated and control plants were detected for most studied characters in M1 and M2 genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 30 publications
8
42
1
Order By: Relevance
“…With refer to irradiation effects, it was appeared that proline content was reduced with increasing either gamma or laser level in both generations. The present findings are similar to those of Hamideldin and Eliwa (2015) and Hanafy and Akladious (2018) used gamma-radiation, also Perveen et al (2011) used laser-ways.…”
Section: Proline Contentsupporting
confidence: 93%
“…With refer to irradiation effects, it was appeared that proline content was reduced with increasing either gamma or laser level in both generations. The present findings are similar to those of Hamideldin and Eliwa (2015) and Hanafy and Akladious (2018) used gamma-radiation, also Perveen et al (2011) used laser-ways.…”
Section: Proline Contentsupporting
confidence: 93%
“…Low to mediate doses of gamma radiation found to be positively effective on growth parameters and yield of fenugreek crop (Hanafy and Akladious, 2018). Irradiation with low to mediate doses may be profitable for improving physiological and biochemical processes in irradiated plants as recognized earlier (Borzouei et al, 2013).…”
Section: Introductionmentioning
confidence: 81%
“…Concerning the effect of irradiation, Hanafy and Akladious (2018) found that the progressive increase in growth and yield parameters of irradiated fenugreek plants was detected with gamma doses from 25 to 200 Gy, but dose 100 Gy was found to be the most effective one. Also, they recorded growth inhibition of irradiated plants exposed to 400 Gy below that of the un-irradiated control.…”
Section: Growth and Yield Parametersmentioning
confidence: 99%
“…Treating plants with highest doses of gamma rays resulted in the highest reduction in content of genomic DNA. Similarly, the appearance or disappearance of bands under gamma irradiation might be considered as molecular markers for radiation processes 34 . It has been exhibited that effects of gamma rays on ISSR fingerprinting might be connected to structural rearrangements in DNA caused by different types of DNA damages 35 .…”
Section: Primer Namementioning
confidence: 99%